2014
DOI: 10.1089/thy.2014.0153
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Induces Overexpression of Immediate Early Genes in Active Graves' Ophthalmopathy

Abstract: IEGs, IL-1B, and IL-6 were overexpressed in smokers with severe active GO compared to nonsmokers, suggesting that smoking activates pathways associated with adipogenesis and inflammation. This study underlines the importance of IEGs in the pathogenesis of GO, and provides evidence for possible novel therapeutic interventions in GO. The mechanisms activated by smoking may be shared with other conditions such as rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 40 publications
3
19
0
2
Order By: Relevance
“…We have recently demonstrated that several immediate early genes including CYR61, EGR1 and COX-2 are overexpressed in orbital tissue of smokers with severe GO as compared to nonsmokers [21]. Tobacco smoking is a risk factor for development of both GD and GO, and it was stated in a recent review that current smoking increases the risk of GD approximately twofold and GO approximately threefold [3].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that several immediate early genes including CYR61, EGR1 and COX-2 are overexpressed in orbital tissue of smokers with severe GO as compared to nonsmokers [21]. Tobacco smoking is a risk factor for development of both GD and GO, and it was stated in a recent review that current smoking increases the risk of GD approximately twofold and GO approximately threefold [3].…”
Section: Discussionmentioning
confidence: 99%
“…36 Upregulation of several adipocyte regulatory genes including PPARc, adiponectin, and leptin support increased de novo adipogenesis and/or fat cell expansion in TO. 6 In addition, adipogenesis may be regulated through Wnt-signaling with dysregulation of secreted frizzled-related protein-1, Wnt5a, sFRPs, and DKK.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is related to an increased risk of Graves’ hyperthyroidism (twofold), GO (three to four times), or relapse of GD or GO (48, 49), and it is linked to a more severe GO. Many different hypotheses about how smoking may enhance the risk of GD or GO have been reported (5058). …”
Section: Environmental Factorsmentioning
confidence: 99%